Remotely sensed primary productivity shows that domestic and native herbivores combined are overgrazing Patagonia. Issue 7 (24th May 2019) - Oliva, Gabriel; Paredes, Paula; Ferrante, Daniela; Cepeda, Carla; Rabinovich, Jorge
Abstract: Carrying capacity is the maximum animal density an area can sustain without deterioration of its resources. Overgrazing has degraded Patagonia, but sheep stocks decreased and gave way to mixed systems with cattle, goats and guanacos (native wild camelids). The objective of this paper was to develop a method to estimate the carrying capacity based on the remotely sensed data, and to assess wild and domestic herbivore numbers in order to establish if grazing stocks have evolved to balance with carrying capacity. Net Primary Productivity (NPP) MOD17/A3 images and field Aerial Net Primary Productivity (ANPP) data of 66 sites were linearly regressed ( R 2  = 0.83, p  < 0.01), and the slope 0.236 used to convert MOD17/A3 NPP to ANPP. Harvest index (proportion of ANPP that may be sustainably consumed) was estimated as a function of ANPP and carrying capacity as a consumable forage/estimated annual consumption, set at 500 (sheep and goats), 3, 200 (cattle) and 750 kg Dry Matter head −1  year −1 (guanacos). Regional ANPP ±  SD (2000–2015) was 758 ± 52 kg Dry Matter ha −1  year −1 and Harvest index was 13.7 ± 0.6%. Regional carrying capacity was 14.8 ± 1.6 M sheep or goats, 2.3 ± 0.3 M cattle or 9.9 ± 1.2 M guanacos. Domestic stock was high from 1920 to 1980, but declined thereafter and remained mostly within 1 SD of mean 2000–2015 carrying capacity. In this century, annual provincial stocks and carrying capacity correlated well ( R 2  = 0.94, p  < 0.01) with a slope close to 1. Guanacos increased from 0.5 to 2 M between 2000 and 2015, driving linearly combined grazing pressures 36% and 62% above carrying capacity in southern Patagonia provinces in 2015. Synthesis and applications . From the year 2000, after decades of sheep overstocking, domestic stock has shown a regional trend towards a grazing equilibrium, but growth of guanacos might have upset that trend. Participation of guanacos as a critical excess in total grazing pressure is debatable, but management of these populations is necessary and may be increasingly attractive if combined production systems are developed to incorporate wild meat and fibre. Our method, MOD17/A3 enables a carrying capacity evaluation and stock adjustment in these unique mixed grazing systems, preventing further rangeland degradation and loss of ecosystem services. Abstract : From the year 2000, after decades of sheep overstocking, domestic stock has shown a regional trend towards a grazing equilibrium, but growth of guanacos might have upset that trend. Participation of guanacos as a critical excess in total grazing pressure is debatable, but management of these populations is necessary and may be increasingly attractive if combined production systems are developed to incorporate wild meat and fibre. Our method, MOD17/A3 enables a carrying capacity evaluation and stock adjustment in these unique mixed grazing systems, preventing further rangeland degradation and loss of ecosystem services. Abstracto: La capacidad de carga es la densidad animal máxima que un área puede sostener sin deteriorar sus recursos. El sobrepastoreo ovino ha degradado la Patagonia pero se redujo recientemente y dio lugar a sistemas con bovinos, cabras y guanacos (camélidos nativos silvestres). Nuestro objetivo fue desarrollar un método de estimación de capacidad de carga general con sensores remotos y comparar estas estimaciones con cargas animales para evaluar si han llegado a un equilibrio. La regresión entre productividad primaria neta (NPP) de imágenes MOD17/A3 y productividad primaria neta aérea (ANPP) de 66 sitios de campo es significativa ( R 2  = 0.83, p  < 0.01) con pendiente 0.236, que se utilizó para convertir NPP MOD17/A3 en ANPP. El índice de cosecha (proporción consumible de ANPP) se calculó en base a la biomasa de herbívoros en Sud América, y la capacidad de carga como forraje consumible/consumo anual estimado animal −1, fijado en 500 (ovinos y caprinos), 3, 200 (bovinos) y 750 kg Materia Seca . cabeza −1. año −1 (guanacos). La ANPP ± DS (2000–2015) regional fue de 758 ± 52 kg MS . ha −1. año −1, el índice de cosecha 13.7 ± 0.6%, la capacidad de carga de 14.8 ± 1.6 M ovinos o caprinos, 2.3 ± 0.3 M bovinos o 9.9 ± 1.2 M guanacos. Entre 1920 a 1980 las existencias ganaderas fueron elevadas, pero entre 2000–2015 se mantuvieron ±1DS de la capacidad de carga y ambas variables correlacionaron bien ( R 2  = 0.94, p  < 0.01, pendiente cercana a 1). Los guanacos incrementaron de 0.5 M a 2 M (2000–2015), colocando la presión de pastoreo linealmente combinada 36%–62% sobre la capacidad de carga en dos provincias en 2015. Síntesis y aplicaciones . Después de décadas de sobrepastoreo, las existencias domesticas muestran convergencia con la capacidad de carga a partir del año 2000, pero el crecimiento del guanaco pudo haberlas desbalanceado. La participación de guanacos en el exceso de presión de pastoreo es todavía debatible, pero el manejo de estas poblaciones es necesario y podría ser atractivo bajo sistemas de producción combinados que incorporen carne y fibra nativa. MOD17/A3 permite un cálculo de capacidad de carga para planificar estos sistemas mixtos, de modo de prevenir la degradación de pastizales y pérdida de servicios ecosistémicos.